Sikap Kritis Negara Berkembang terhadap Hukum Internasional - M. Gaffar, Janedjri (Mahkamah Konstitusi Republik Indonesia, 2013)
International law is a political instrument of developed states to intervene developing states. Law can function for numerous interests such as, inter alia, a political instrument. Intervention of developed countries to developing states can happen in two ways which both ways cannot be regarded as violation of international law. The involvement of a state in an international agreement denotes that the country intentionally burdens itself to carry out obligation that has been agreed upon as stated in the agreement. One of the obligations is to transform the contents of the agreement to its national law. The involvement of developing countries in international law is an intention to create breakthrough to face competition with developed states. With the existence of WTO, developing states can defend their rights which are violated and can force developed states to negotiate. The availability of legal remedy provide strength to developing states to force developed states in particular cases.